PERCEPTIONS, PRACTICES, AND ASSESSMENT LITERACY NEEDS OF EFL TEACHERS: ENHANCING READING LITERACY INSTRUCTION UNDER AKM POLICY - Fakhira, Jihan; Zulaiha, Siti (University of Kuningan, 2024)
Since the discontinuation of national examinations (UN) in 2020, the Indonesian Government introduced the Minimum Competency Assessment (Asesmen Kompetensi Minimum-AKM) to assess students' fundamental abilities. Consequently, teachers are pivotal in integrating AKM-based reading literacy questions to enhance students' reading skills. This study aims to explore teachers' perceptions, practices, and assessment literacy needs concerning teaching and assessing students' reading literacy based on AKM. Ten EFL junior high school teachers participated in interviews. Findings revealed varying perceptions among teachers regarding AKM. While some supported the policy for its positive impact on students and learning, others doubted its effectiveness for certain reasons. In terms of teaching and assessment practices, most teachers partially integrate the three components of AKM reading literacy into their classrooms. They also utilize various stimuli and question types similar to those in AKM, yet complex multiple-choice assessments are underutilized. Lastly, teachers expressed diverse literacy assessment needs, including strategies for teaching reading, designing critical reading questions, creating stimulus materials, gaining AKM knowledge, enhancing student interest in reading, and identifying intended learning outcomes to improve their teaching and evaluation of students' literacy.